STRATEGI PEMBELAJARAN UNTUK ANAK BERKESULITAN BELAJAR DI SEKOLAH INKLUSIF - Nafia Wafiqni; Neli Rahmaniah; Asep Supena (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
Learning difficulties (learning disabilities) are one of the obstacles that children with special needs experience in their learning process. So that children with special needs may have their learning rights realized and not disrupt the learning process for other typical kids, the government implemented an inclusive program in public schools. The purpose of this study is to describe the learning conditions implemented for students with learning disabilities and explain the learning strategies carried out by teachers for students with learning disabilities in inclusive schools. This study used a qualitative research method with a case study approach, conducting an in-depth study of learning strategies for students with learning disabilities at Public Elementary School (SD) 01 Bojongsari Depok. The three stages of data analysis carried out by researchers are data collection, data reduction, data presentation, and drawing conclusions. The results showed that the learning conditions of students with learning disabilities were that they lacked focus during learning and their attention was easily distracted. They were not yet independent and had difficulty in counting, spelling, reading, or writing. Learning strategies carried out by teachers in dealing with students with learning disabilities in Elementary School (SD) Negeri 01 Bojongsari Depok, such as using an adaptive curriculum approach, special services with learning methods (auditory-visual, repetition of regular class material, question and answer, and remedial), reducing the level of difficulty of questions and material as well as minimum completeness criteria, and selection of special learning media for students with learning disabilities such as word cards, blocks of numbers and letters, miniature fruits or animals, and others.